PENINGKATAN MINAT DAN HASIL BELAJAR SISWA TERHADAP MATERI FISIKA MELALUI MODEL PROJECT BASED LEARNING - Farista, Sendi; Suseno, Nyoto; Rosa, Friska Octavia; Harjati, Purwiro (Universitas Muhammadiyah Metro, 2022)
Abstract : This study aims to determine the effect of using the Project Based Learning (PjBL) model on increasing student interest and learning outcomes, knowing student responses to the process of learning activities using the PjBL model, and knowing the high percentage of student learning outcomes obtained from using the PjBL model. The research method used is Classroom Action Research (CAR), carried out in two cycles with four stages. The stages in question are planning, implementation, observation, and reflection. The subjects of this study were students of class X MIA 1 SMAN 1 Purbolinggo in the 2021-2022 academic year. The data analysis technique used is effect size analysis, student response analysis, and analysis of student learning outcomes. The results of the study include: the use of the PjBL model affects increasing student interest in learning with a known effect size of 0.2298 in cycle 1 and 0.439 in cycle 2, and the use of the PjBL model affects improving student learning outcomes with a known effect size of 0.499 in cycle 1 and 0.71 in cycle 2, students like the process of learning activities using the PjBL model, the high percentage of completeness of student learning outcomes from using the PjBL model is 67.6% with 23 students completing cycle 1 and 87% with 28 students completing cycle 2 . Suggestions for similar research to be carried out include: it is necessary to research on improving aspects of interest and other learning outcomes using different subject matter. It can be done using two different classes to determine the effect of implementing the PjBL model so that differences or comparisons can be known.Keywords: Interest in Learning, Learning outcomes, Project Based Learning (PjBL) model.